The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2015
DOI: 10.1016/j.jsat.2014.12.006
|View full text |Cite
|
Sign up to set email alerts
|

Gender-based Outcomes and Acceptability of a Computer-assisted Psychosocial Intervention for Substance Use Disorders

Abstract: Background Digital technologies show promise for increasing treatment accessibility and improving quality of care, but little is known about gender differences. This secondary analysis uses data from a multi-site effectiveness trial of a computer-assisted behavioral intervention, conducted within NIDA's National Drug Abuse Clinical Trials Network, to explore gender differences in intervention acceptability and treatment outcomes. Methods Men (n=314) and women (n=192) were randomly assigned to 12-weeks of tre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
5
1

Year Published

2017
2017
2021
2021

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 15 publications
(7 citation statements)
references
References 45 publications
1
5
1
Order By: Relevance
“…Most aims of the interventions stated in the studies have not been evaluated rigorously. For instance, only 19 out of 36 completed studies were RCTs, and only eight of them ensured comparability by involving a nonblended intervention control group with the same number of sessions [ 27 , 50 , 57 , 62 , 70 , 75 , 78 , 83 ]. Only eight studies were considered high quality studies, and only six studies involved a control group big enough to detect effect sizes of d =0.35 or less.…”
Section: Discussionmentioning
confidence: 99%
“…Most aims of the interventions stated in the studies have not been evaluated rigorously. For instance, only 19 out of 36 completed studies were RCTs, and only eight of them ensured comparability by involving a nonblended intervention control group with the same number of sessions [ 27 , 50 , 57 , 62 , 70 , 75 , 78 , 83 ]. Only eight studies were considered high quality studies, and only six studies involved a control group big enough to detect effect sizes of d =0.35 or less.…”
Section: Discussionmentioning
confidence: 99%
“…This was in line with previous studies conducted in Malaysia [ 12 ] and Jordan [ 49 ]. The likely explanation could be related to differences in health behavior as well as acceptance of recommendation between males and females [ 50 , 51 ].…”
Section: Discussionmentioning
confidence: 99%
“…Behavior therapy studies have generally found that women and men respond similarly to these treatments across a wide array of treatment types and substances, including cognitive-behavioral therapies, contingency management, and behavioral couples therapy (Burch, Rash, & Petry, 2015; Campbell et al, 2015; DeVito et al, 2014; Rash & Petry, 2015). The use of mutual-help groups, such as Alcoholics Anonymous, has been shown to help both men and women without evidence of significant differences (Ammon, Bond, Matzger, & Weisner, 2008).…”
Section: Treatment Of Substance Use Disorders In Womenmentioning
confidence: 99%